A Study on State of Charge Estimation Method for Lithium Carbon Fluorides Primary Batteries. Issue 12 (1st December 2022) - Liu, Wen; Fu, Shiyi; Li, Yong; Wan, Bingxin; Wu, Chao; Guo, Rui; Pei, Haijuan; Xie, Jingying
Abstract : Recently, lots of work has been focused on the state of charge (SOC) estimation of lithium-ion batteries. However, such little research has been on the SOC estimation of primary batteries. The non-rechargeable trait of primary batteries induces accurate, reliable and non-destructive SOC estimation one of the critical tasks for their application, especially for long time storage. In this work, three kinds of lithium carbon fluorides (Li/CF x ) batteries (>3Ah) with different cathode material and design of batteries have been prepared, all of which can discharge at 1C. The energy density of the modified pouch cell with a capacity of 9Ah can reach 511 Wh kg −1 at 1C. Furthermore, four types of open circuit voltage (OCV) models (34 models) are employed to estimate the SOC of Li/CF x batteries for the first time. The OCV fitting error of polynomial models can be limited within ±0.05 V. And the corresponding SOC estimation results outperform other models, showing high accuracy. At last, the applicability of the proposed OCV based SOC estimation method are verified.